Investigating the growth trend of biomedical production in Iran and futurology to achieve the horizon of 1404 - Hannane Hoseinzade; Hossein Rastegar; Majid Annabi; Ali Razzazan (Tehran University of Medical Sciences, 2023)
Background Biomedical drugs have been considered by many countries due to their important effect and high value. In the upstream documents, achieving a share of 3% of the global market of these drugs is set for 1404.The purpose of this study is to calculate the growth rate of biomedical products, their import rate and suggest strategies to reach the specified horizon. Materials and Methods This research consists of two parts, quantitative and qualitative, in which the exploratory approach and the theorizing and typology model have been used. In the "quantitative" section, according to the country's pharmaceutical statistics, the growth trend of production and import of biopharmaceuticals over the past decade was calculated. The next step was performed "qualitatively" using the data research method of the grounded theory. First, information about the country's biopharmaceutical market was collected through interviews with 25 experts in this field. Then the "key templates" became the appropriate model. Results The results of the present study in the qualitative section were the extraction more than 326 open codes which is presented in the form of a paradigm model. In the quantitative sector, Iran's global share was estimated at 0.5% to 0.7%, which is growing with an average numerical growth of 5.6% and 30% in Rial. The average global market growth was estimated at 8.2% per year. Conclusion Considering Iran's 0.5% share of the world market, with the continuation of the current trend, it is not possible to achieve the set horizon and to achieve this horizon, we need a leap in pharmaceutical biotechnology.